2020
DOI: 10.1093/jamia/ocaa284
|View full text |Cite
|
Sign up to set email alerts
|

Virtual care expansion in the Veterans Health Administration during the COVID-19 pandemic: clinical services and patient characteristics associated with utilization

Abstract: Objectives To describe the shift from in-person to virtual care within Veterans Affairs (VA) during the early phase of the COVID-19 pandemic, and to identify at-risk patient populations who require greater resources to overcome access barriers to virtual care. Materials and Methods Outpatient encounters (N = 42,916,349) were categorized by care type (e.g. primary, mental health, etc.) and delivery method (e.g., in-person, vid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
223
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 177 publications
(246 citation statements)
references
References 28 publications
21
223
2
Order By: Relevance
“…Other recent studies have explored different aspects of COVID-19 era telehealth utilization for selected clinical conditions 32 and specific patient groups. 33 The Centers for Disease Control and Prevention 34 recently reported results relying on data furnished by a sample of telehealth companies. To the best of our knowledge, our study is the first that follows a large, well-defined continuously insured national cohort of patients to offer an assessment of individual, clinical, practitioner, payer, and geographical factors associated with changing patterns of telehealth use at the onset of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Other recent studies have explored different aspects of COVID-19 era telehealth utilization for selected clinical conditions 32 and specific patient groups. 33 The Centers for Disease Control and Prevention 34 recently reported results relying on data furnished by a sample of telehealth companies. To the best of our knowledge, our study is the first that follows a large, well-defined continuously insured national cohort of patients to offer an assessment of individual, clinical, practitioner, payer, and geographical factors associated with changing patterns of telehealth use at the onset of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…11 We defined priority group in this analysis by 4 categories: high-disability veterans, low-/moderate-disability veterans, low-income veterans, and veterans with no service-related disability, as defined previously. 13 We used the Charlson Comorbidity Index without age as a proxy for patient comorbidities at baseline. 14,15 We defined each condition in the Charlson Comorbidity Index using relevant International Classification of Diseases, Tenth Revision codes 16 retrieved from health care encounters from January 1, 2018, through December 31, 2019, such that all comorbidities preceded COVID-19 testing.…”
Section: Veteran Demographic Characteristics and Comorbiditiesmentioning
confidence: 99%
“…In line with that, studies that evaluated telemedicine proposed that older and rural patients, as well as patients with lower median household incomes might face difficulties in using these high-tech technologies. 23 , 24 Furthermore, Jazieh et al reported that medical centers in lower-income countries were less likely to hold virtual tumor boards and run virtual clinics. 16 …”
Section: Discussionmentioning
confidence: 99%